2017
DOI: 10.1007/s10068-017-0006-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and starch characteristics of the Japonica rice mutant variety Seolgaeng for dry-milled flour

Abstract: Producing good-quality, fine rice flour is more difficult than wheat flour because the rice grain is harder. The non-glutinous -type variety Seolgaeng, derived from N-methyl-N-nitrosourea (MNU) mutagenesis, and four other varieties, representing a range of amylose contents, were evaluated in this study. Dry-milled Seolgaeng rice flour exhibited an average particle size that is<70 μm, a more uniform particle-size proportion than other varieties. Moreover, we noted significant differences in the damaged starch c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The chain–length distributions of amylopectin from wild-type and mutants endosperm were analyzed using HPAEC - PAD as in previous reports (Hanashiro et al 1996 ; Kwak et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The chain–length distributions of amylopectin from wild-type and mutants endosperm were analyzed using HPAEC - PAD as in previous reports (Hanashiro et al 1996 ; Kwak et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The latter has “floury endosperm ( flo7 )” that is easily ground in small-scale mills [ 5 ]. Seolgaeng yields milky, flavorful, non-glutinous rice grains conducive to brewing and dry milling for rice flour [ 6 , 7 , 8 ]. Hangaru was developed by hybridizing Daeripbyeo and Seolgaeng.…”
Section: Introductionmentioning
confidence: 99%
“…Hangaru was developed by hybridizing Daeripbyeo and Seolgaeng. The former bears large grains, whereas the latter is a high-quality Japonica generated by mutating fertilized ovules with N -methyl- N -nitrosourea (NMU) [ 6 , 7 , 8 ]. Shingil was derived from the mutation of Hanareum with NMU [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The other genomic research using two Tongil-like varieties also showed japonica-type SNP pattern on common japonica-type region on chromosome 6 [40]. Tongillike varieties showed medium amylose contents, approximately 19~20%, which is similar with that of non-waxy Korean japonica varieties [41,42]. Further, Os06g0130400, one of the selected genes in Chr6-1, also was reported as the gene controlling starch grain size in endosperm [43].…”
Section: Discussionmentioning
confidence: 88%